Kontribusi Pendidikan Agama terhadap Kesadaran Sosial dan Kebersamaan dalam Masyarakat di Perumahan Vila Dago Tol Serua Ciputat - Rachmatullah Rusli; Ahmad Nana Mahmur Mulyana (Lembaga Pengembangan Kinerja Dosen, 2025)
This study investigates the contribution of religious education to social awareness and togetherness in multicultural urban communities, specifically at Vila Dago Tol Serua Ciputat Housing. The research addresses the challenge of building social cohesion in heterogeneous residential communities where residents from diverse social, economic, and cultural backgrounds coexist. A qualitative descriptive approach was employed, utilizing in-depth interviews with religious leaders, RT/RW officials, and housing residents, along with direct observation of social interaction patterns. Data analysis was conducted thematically following Clarke & Braun's approach to identify key patterns related to religious education and social awareness. The findings reveal that religious education significantly transforms residents' social behavior, increasing care, tolerance, and mutual cooperation. Religious activities achieve 75% participation among household heads, with 80% correlation between religious participation and social community involvement. The internalization of ukhuwah (brotherhood) values effectively bridges social, economic, and cultural differences among residents. Religious education functions as an effective conflict prevention mechanism, with no serious inter-resident conflicts occurring in the past three years. The integrative approach combining religious rituals with real social action creates sustainable social transformation. Religious education contributes significantly to building social awareness and togetherness in multicultural urban communities through consistent implementation of universal values of tolerance, empathy, and social responsibility.